Stereochemistry of organic compound : Principles and applications - Nasipuri, D. (New Delhi: New age international, 2011)
This text deals with the new concepts and terminology that have been introduced into the treatment of organic stereochemistry over the last decade. Organic reaction mechanisms, as they relate to stereochemistry, are included, and the pericyclic reaction using the frontier molecular orbital approach is explained. The text does not assume a strong grounding in organic chemistry and will therefore be useful to a broader spectrum of students - both graduate and undergraduate. The volume features numerous illustrations and programmed problems.
Include bibliographical references; Index 521-537p.
Keywords: Molecular recognition; Organic chemistry; Stereochemistry; Chemistry